2003
DOI: 10.1212/01.wnl.0000055862.20003.4a
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal neuropsychological study of partial brain radiation in adults with brain tumors

Abstract: Partial brain fractionated RT was not associated with adverse neuropsychological effects through the first 2 years following therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(72 citation statements)
references
References 24 publications
3
64
0
5
Order By: Relevance
“…In cross-sectional studies, clear-cut cognitive defi cits after focal radiotherapy have rarely been reported, and then only with a short follow-up. 8,[16][17][18][19][20][21][22][23] One study reports selective cognitive defi cits 6 years after treatment with focal radiotherapy, 23 whereas two other studies report few cognitive sequelae 6 years or more after radiotherapy. 8,9 However, in our study, which had a mean follow-up of 12 years, we found signifi cant deterioration in the domain of attentional functioning in patients who received radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cross-sectional studies, clear-cut cognitive defi cits after focal radiotherapy have rarely been reported, and then only with a short follow-up. 8,[16][17][18][19][20][21][22][23] One study reports selective cognitive defi cits 6 years after treatment with focal radiotherapy, 23 whereas two other studies report few cognitive sequelae 6 years or more after radiotherapy. 8,9 However, in our study, which had a mean follow-up of 12 years, we found signifi cant deterioration in the domain of attentional functioning in patients who received radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have concluded that factors other than radiotherapy account for cognitive sequelae in patients with LGG. 17,18,21,33 We previously reported that, among other things, the tumour seems to contribute to the development of late cognitive defi cits in patients with LGG. Because the patients in our study were not randomly assigned according to their radiotherapy status, no defi nite answer can be given as to whether the reported cognitive deterioration is exclusively due to radiotherapy.…”
Section: Radiotherapy Patientsmentioning
confidence: 96%
See 1 more Smart Citation
“…Neuropsychological test results revealed 80% of the patients exhibited impaired memory, approximately 33% manifested slowed visuomotor speed, executive dysfunction, and poor fine motor dexterity. Others have failed to find significant late-delayed neurocognitive dysfunction as a result of radiotherapy (Vigliani et al, 1996;Torres et al, 2003). Differences in reported radiotherapy-associated cognitive dysfunction (incidence estimates that vary from 0 to 86%) may in part be related to differences in treatment variables, study methodology, and the disease that is being treated.…”
Section: Radiotherapymentioning
confidence: 99%
“…32 Recently, a definitive cognitive decline in 17 adult patients receiving partial brain irradiation was not seen through the first 2 years after RT. 33 The potential shortcoming of this study, and the likely reason it did not show a definitive decline in function, is that patients receiving partial brain irradiation were treated as a homogenous population. Partial brain irradiation and the gradients of radiation dose created by it can vary greatly between individuals, their tumors, and tumor histologies.…”
mentioning
confidence: 95%